(untitled) (Fiep Bulletin - online, 2014)
LMS method has been used to build curves of anthropometrics measures such as height. LMS assumptions are related to Box-Cox transformation for positive independent values for age groups in order to normalize skewed distributions, typically find in indicators of body composition. The aim of this paper is, by a systematic review, to identify and to describe the main characteristics of studies in witch the LMS method was used for construction of reference centiles curves, in the last 5 years. A Systematic review has been carried out using the MEDLINE database and the key-word LMS method as search strategy. The “limits adjusted” in the MEDLINE contemplated human beings, men and women and articles published in the last 5 years. 31 studies satisfied the inclusion criteria. These studies were carried out in countries such as India, China, Japan, Korea, Taiwan, Iran, Israel, Turkey, Morocco, Australia, Great-Britain, Italy, Denmark, Holland, Bangladesh, Ireland, The United States, Brazil and Argentina. The majority of them constructed references centiles curves for children and adolescents with anthropometrical measures such as body mass, height and body mass index. Others measures so had been used such as waist circumference, head circumference, hip circumference, sitting height, Inferior limb length, as well physiological and body composition variables as arterial blood pressure, total energy expenditure and bony mineral content. These reference centiles build using the LMS method is useful for growth monitoring, assessment of nutritional status and for other diagnostics related to risk of diseases. Thus, the LSM method seems to be a useful method for the construction of centiles curves for variables asymmetrically distributed.